Uramphite from the Nova Ves pod Plesi (Czech Republic), the third world occurrence - description and vibrational spectroscopy - Sejkora,J.; Kristek,J.; Skacha,P.; Dolnicek,Z. (Journal of Geosciences, 2024)
We have studied the rare ammonium uranyl phosphate mineral, uramphite, from the small uranium occurrence Nova Ves pod Plesi, central Bohemia (Czech Republic). It has been found on a few specimens and forms rare groups up to 1 mm in size in small vugs of limonite veins in altered rocks in association with meta-autunite, metatorbenite and churchite-(Y). Uramphite is pale yellow to light greenish yellow with a pale yellow streak and shows weak fluorescence in a pale yellow hue under 254 nm and 366 nm UV-radiation, respectively. Uramphite crystals are transparent to translucent and have an intensive vitreous luster. The mineral is very brittle and at least one system of perfect cleavage along {001} was observed. The quantitative electron-microprobe chemical analyses of uramphite agree well with the proposed ideal composition and correspond to the following empirical formula [(NH4)0.79Na0.12K0.07Ca0.03]Σ1.01(UO2)1.00(PO4)1.00·3H2O (on the basis of 1 P atom pfu). Uramphite is tetragonal, space group P4/ncc, with the unit-cell parameters refined from X-ray powder diffraction data: a = 7.0292(11), c = 18.092(2) Å, V = 893.9(2) Å3. Vibrational (Raman and infrared) spectroscopy documented the presence of molecular water, ammonium, uranyl, and phosphate groups in the crystal structure of uramphite.
Keywords: uramphite; meta-autunite group; chemical composition; Raman spectroscopy; infrared spectroscopy; Nova Ves pod Plesi